Landscape anastasis transforming the decommissioned San Mateo Sanitary Landfill through a regenerative ecological complex - Almodal, Inna Isabel T.; Villajuan, Jose Dan V. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The recent turnover of the decommissioned San Mateo Sanitary Landfill to the Department of Environment and Natural Resources has opened an opportunity in the Rizal province for its development into an ecological complex. This study explores how landscape architecture could contribute to the post-closure measures and development of the landfill. The primary goal of the thesis was to determine and develop the post-closure use of the site through strategies and methods involving land suitability analysis as well as concepts in ecological planning and design. Landscape anastasis - pertaining to the revival or rebirth of a degraded landscape -- was the unifying concept utilized in the study. The landscape design synthesis reflected how the landfill could be transformed from a degraded site to a restored and functional site that would raise the awareness of people with regard to landscape reclamation and landfill rehabilitation.
includes appendices.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman